Tarsal metric trends over the Medieval-Post-Medieval transition in London - Malorie E. Albee (Homo)
The Medieval-Post-Medieval transition in England was an important shift in the human biocultural environment. With urbanization and industrialization came resultant changes in living and working conditions and subsequent effects on the skeleton. In addition, the Post-Medieval period ushered in changes in footwear and activity patterns, with potential consequences on foot bone morphology. The objective of this study is to compare calcaneal and talar lengths between the Medieval and Post-Medieval periods to determine whether there are quantifiable differences that correspond to shifting footwear and activity patterns. T-tests and ANCOVAs (and their non-parametric equivalents) were used to compare calcaneal and talar lengths of 1086 adults from 14 London cemeteries (Medieval n = 8, Post-Medieval n = 6), available in the Oracle Wellcome Osteological Research Database (WORD) curated by the Museum of London. Males and females were also analyzed separately. In the total sample, tali and calcanei are longer in the Medieval period (p < 0.001 for both tarsals). When males and females are analyzed separately, male talar length is greater in the Post-Medieval period (p < 0.001). The difference in talar length between periods is not statistically significant for females (p = 0.093). These differences in talar and calcaneal lengths between periods likely reflect differences in footwear between the Medieval and Post-Medieval periods. The magnitude of these differences varies according to sex, indicating that the change in footwear had differential impacts on men and women. Together, these results suggest that Medieval and Post-Medieval tarsals physically incorporated their respective cultural environments and gendered differences in cultural practice, particularly related to the footwear characteristic of each period.